From Melusine to the child-woman: André Breton’s defense of women in power in Arcane 17 - Ornelas, Fernanda Taís (Lettres Françaises, 2019)
The poetic narrative Arcane 17 was written by André Breton in 1944, period of France’s liberation from the Nazi occupation, which provoked in the leader of Surrealism a feeling of hopefulness which is reflected in his work. Accordingly to this aspect, the presente article aims to analyze two feminine symbols present in Arcane 17 – the legendary character Melusine and the stereotype of the child woman, popularized by the novel La Femme-Enfant: roman contemporain (1891), by Catulle Mendès –, with the aim of demonstrating Breton’s disenchantment towards the patriarchy, as well as the surrealist’s defense in favor of the substitution of men’s power by that of women, revolutionary and unusual positioning for the time the work was written.